Postantibiotic Effects of Grepafloxacin Compared to Those of Five Other Agents against 12 Gram-Positive and -Negative Bacteria - Spangler, Sheila K. (American Society for Microbiology, 2000)
The postantibiotic effect (PAE) (10× the MIC) and the postantibiotic sub-MIC effects (0.125, 0.25, and 0.5× the MIC) were determined for six compounds against 12 strains. Measurable PAEs ranged between 0 and 1.8 h for grepafloxacin, 0 and 2.2 h for ciprofloxacin, 0 and 3.1 h for levofloxacin, 0 and 2.2 h for sparfloxacin, 0 and 2.4 h for amoxicillin-clavulanate and 0 and 4.8 h for clarithromycin. Reexposure to subinhibitory concentrations increased the PAEs against some strains.